Mass Spectrometry–Based Escherichia coli H Antigen/Flagella Typing: Validation and Comparison with Traditional Serotyping. (6th January 2020) - Cheng, Keding; She, Yi-Min; Chui, Huixia; Domish, Larissa; Sloan, Angela; Hernandez, Drexler; McCorrister, Stuart; Ma, Jun; Xu, Bianli; Reimer, Aleisha; Knox, J David; Wang, Gehua
Abstract: BACKGROUND: Escherichia coli H antigen typing with antisera, a useful method for flagella clinical identification and classification, is a time-consuming process because of the need to induce flagella growth and the occurrence of undetermined strains. We developed an alternative rapid and analytically sensitive mass spectrometry (MS) method, termed MS-based H antigen typing (MS-H), and applied it at the protein sequence level for H antigen typing. We also performed a comparison with traditional serotyping on reference strains and clinical isolates. METHODS: On the basis of international guidelines, the analytical selectivity and sensitivity, imprecision, correlation, repeatability, and reproducibility of the MS-H platform was evaluated using reference strains. Comparison of MS-H typing and serotyping was performed using 302 clinical isolates from 5 Canadian provinces, and discrepant results between the 2 platforms were resolved through whole genome sequencing. RESULTS: Repeated tests on reference strain EDL933 demonstrated a lower limit of the measuring interval at the subsingle colony (16.97 μg or 1.465 × 10 7 cells) level and close correlation ( r 2 > 0.99) between cell culture biomass and sequence coverage. The CV was <10.0% among multiple repeats with 4 reference strains. Intra- and interlaboratory tests demonstrated that the MS-H method was robust and reproducible under various sample preparation and instrumentation conditions. Using discrepancy analysis via whole genome sequencing, performed on isolates with discrepant results, MS-H accurately identified 12.3% more isolates than conventional serotyping. CONCLUSIONS: MS-H typing of E. coli is useful for fast and accurate flagella typing and could be very useful during E. coli outbreaks.